Patients' sense of support within the family in the palliative care context: what are the influencing factors?. Issue 12 (13th May 2014) - Milberg, Anna; Wåhlberg, Rakel; Krevers, Barbro
Abstract Objective Mutual support within the family is of great importance to maintain its proper functioning. The study aim, which was based on a family system approach, was to evaluate which variables are associated with patients' sense of support within the family in the palliative care context. Methods We recruited 174 adult patients (65% of those eligible) from six palliative home care units, who had non‐curable disease with an expected short‐term survival, such as disseminated cancer or non‐malignant diagnosis. The relationship between the endpoint and individual factors were evaluated in a stepwise model‐building procedure using generalised linear model (ordinal multinomial distribution and logit link). Results The respondents' ratings of their sense of support within the family ranged from 1 (never) to 6 (always), with a mean value of 5.2 (standard deviation 1.06). Patients who less frequently sensed family support experienced more often stress, worry about their private economy, lower self‐efficacy, lower sense of security with palliative care provided (lower ratings on subscales of care interaction, mastery and prevailed own identity), more often anxiety, less often perceived general well‐being for closest ones and less often sense of support from more distant family members. In the model building, three variables were selected to predict the patients' sense of support within the family. Conclusions The dying patients' sense of support within the family related to several factors, and these may help the palliative care teams to identify patients at risk and to alleviate suffering, for example, through supporting the closest family members. Copyright © 2014 John Wiley & Sons, Ltd.